Clinically relevant mechanical testing of hernia graft constructs. (January 2015) - Sahoo, Sambit; DeLozier, Katherine R.; Erdemir, Ahmet; Derwin, Kathleen A.
Abstract: Background: To understand the mechanical behavior of grafts in the context of hernia repair, there is a need to develop and adopt methods for mechanical testing of grafts in a clinically-relevant manner with clinically-relevant outcomes. Materials and methods: Ball-burst and planar-biaxial methods were used to test three commercially-available hernia grafts (DermaMatrix, Biodesign, VitaMesh Blue). Both load-to-failure and cyclic fatigue tests were performed ( n =6–11/group/test). Grafts were tested as sutured constructs in patch geometry. Dilatational strain analysis was performed considering the construct (both test methods) or the graft (planar-biaxial only) as the area of interest. Results: DermaMatrix, Biodesign, and VitaMesh grafts showed differences in mechanical properties at the point of construct failure (load, in-plane load-per-suture and membrane tension) in ball-burst tests and differences in sub-failure properties (stiffness, dilatational strain at 16 N/cm and cyclic mechanical properties) in planar-biaxial tests. In both load-to-failure and cyclic fatigue tests, each graft construct tended to be stiffer in planar-biaxial than ball-burst testing. In biaxial testing, the strain analysis method influenced the mechanical properties with the construct being more compliant than the graft. Conclusions: This study demonstrates that graft-fixation method, test mode and analysis method are important considerations for mechanical characterization of hernia grafts. Ball-burst tests can only estimate construct or material properties, whereas planar-biaxial tests capture anisotropy and can estimate construct, graft and material properties of the same test specimen. When the clinical performance of a graft in the context of hernia repair is of interest, testing a sutured construct and performing construct strain analysis arguably provides the most clinically-relevant assessment method. Graphical abstract: Highlights: Ball-burst and planar-biaxial tests were used to test three types of hernia grafts. Grafts were tested as sutured patch-shaped constructs to model in vivo loading. Both failure and sub-failure properties of the graft and construct were evaluated. Graft-fixation method, test mode and analysis method affect graft biomechanics. Clinically-relevant methods and outcomes are recommended for hernia graft testing.